Synthesis and characterization of (2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate-styrene copolymers and determination of monomer reactivity ratios - Ilter, Z; Özdemir, E; Ahmedzade, M (Vsp Bv, 1999)
Copolymers of (2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate (PDMMA) with styrene were prepared by free radical-initiated solution polymerization in 1,4-dioxane. IR, H-1-NMR, and C-13-NMR techniques were used in the polymer characterization. The copolymer compositions were determined by elemental analysis. Gel permeation chromatography was used for determining the (M) over bar(n), (M) over bar(w), and disparity indices. Glass transition temperatures and thermal properties were determined by differential scanning calorimetry and thermogravimetric analysis, respectively. Reactivity ratios were calculated as r(PDMMA) = 0.183 +/- 0.001. r(St) = 0.34 +/- 0.002 from the Kelen-Tudos equation, and r(PDMMA) = 0.201 +/- 0.042, r(St) = 0.441 +/- 0.220 from the Fineman-Ross equation.
Keywords: (1.3-dioxolane-4-yl)methyl methacrylate; copolymerization; reactivity ratios; Kelen-Tudos method; Fineman-Ross method